Strategi Public Relation dalam Dakwah Perkembangan Media Sosial Pondok Pesantren - Purwanto, Harry; Fuadah, Hilwatul (Institut Agama Islam Syarifuddin Lumajang, 2025)
The development of science and technology has brought very significant changes to every element of human life today. This requires all parties to be able to adapt, especially in developing Islamic preaching in Islamic boarding school educational institutions. Therefore, every Islamic boarding school has Public Relations or Public Relations to develop Islamic preaching and introduce Islamic boarding schools to the outside world. This study aims to analyze the PR (Public Relations) Strategy implemented by the Nurul Haromain Randuagung Islamic Boarding School in developing social media. This type of research uses a qualitative method with a case study approach while in collecting data this study was conducted through in-depth interviews with the managers of the Islamic boarding school's social media. The results of this study examine how the Nurul Haromain Islamic Boarding School utilizes social media platforms to expand the reach of information and improve the quality of the institution. The role of Public Relations (PR) in this Islamic boarding school is very important in managing social media, including creating interesting content, managing interactions with followers, and using social media as a tool to improve the image of the Islamic boarding school. However, the development of this Islamic boarding school's social media has not been optimal. Some of the problems found were content that was less interesting and creative, lack of use of analytical and evaluation tools, and lack of insight into content performance and effective social media strategies. To develop Islamic boarding school social media optimally, strategies are needed such as forming a team with the appropriate skills, creating structured content planning, utilizing analytical features, increasing interaction with followers, collaborating with influencers/religious figures, and utilizing various social media platforms. A comprehensive and sustainable approach is needed so that the Nurul Haromain Islamic Boarding School can utilize social media optimally to expand the reach of preaching, improve its image, and attract the interest of prospective new students.